MAKTAB MUSIQA TA’LIMIDA O‘QUVCHILARNING NAZARIY BILIMLARNI O‘ZLASHTIRISHLARIDA INTERFAOL METOD VA DIDAKTIK O‘YINLARDAN FOYDALANISH - Murodov, M.B. (SCIENCE and SOCIETY, 2023)
The article discusses the importance of using interactive methods and didactic games in the process of acquiring musical theoretical knowledge in the "music culture" classes of secondary schools.
Keywords: music culture; lessons; music theoretical knowledge; interactive method; didactic games; knowledge; students